Rotationally tunable polarization-insensitive single and multifocal metasurface. (22nd March 2019) - Yilmaz, Nazmi; Ozdemir, Aytekin; Ozer, Ahmet; Kurt, Hamza
Abstract: Metasurfaces with superior capabilities to tailor wave fronts of light have become one of the most widely investigated optical elements. Incorporating tunable features into the metasurface design is required. In this study, we have proposed and designed highly efficient rotationally tunable metasurface lens structures inspired by Moiré lenses operating at a 532 nm wavelength. The proposed structures consist of two cascaded all-dielectric metasurfaces, which have reverse phase profiles with respect to each other. The metasurfaces are designed with periodically arranged TiO2 nano-rods on a SiO2 substrate in a square lattice. We demonstrated that the focal length changes nonlinearly according to the mutual rotation of metasurfaces from 30 ° to 150 ° with a focusing efficiency as high as 55% and a wide focal length variation between 11.4 μ m and 4.2 μ m. Moreover, we have designed and proposed a tunable polarization-insensitive multifunctional focal system. Using the proposed multifunctional focal system, focal planes can be formed in consecutive planes and the number of focal planes can be made single or multiple.